Atypical language representation is unfavorable for language abilities following childhood stroke. (January 2019) - Bartha-Doering, Lisa; Novak, Astrid; Kollndorfer, Kathrin; Schuler, Anna-Lisa; Kasprian, Gregor; Langs, Georg; Schwartz, Ernst; Fischmeister, Florian Ph.S.; Prayer, Daniela; Seidl, Rainer
Abstract: Brain plasticity has often been quoted as a reason for the more favorable outcome in childhood stroke compared to adult stroke. We investigated the relationship between language abilities and language localization in childhood stroke. Seventeen children and adolescents with left- or right-sided ischemic stroke and 18 healthy controls were tested with a comprehensive neurolinguistic test battery, and the individual neural representation of language was measured with an fMRI language paradigm. Overall, 12 of 17 stroke patients showed language abilities below average, and five patients exhibited impaired language performance. fMRI revealed increased activity in right hemisphere areas homotopic to left hemisphere language regions. In sum, seven stroke patients revealed atypical, i.e. bilateral or right lateralized language representation. Typical left hemispheric language lateralization was associated with better performance in naming and word fluency, whereas increased involvement of right homologues was accompanied by worse language outcome. In contrast, lesion lateralization or lesion volume did not correlate with language outcome or atypical language lateralization. Thus, atypical language lateralization is unfavorable for language outcome, and right homologues do not have the same cognitive capacity, even in young children. Highlights: We investigated the relationship between language abilities and language localization in childhood stroke. FMRI revealed increased activity in right hemisphere areas homotopic to left hemisphere language regions. Atypical language lateralization was associated with worse language outcome.